PENGARUH KECERDASAN EMOSIONAL TERHADAP KINERJA SUPERVISOR DENGAN EFEKTIFITAS KOMUNIKASI SEBAGAI VARIABEL MEDIASI - RESZHA AZHAR EMAN, MOCHAMMAD (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract: PT Dok dan Perkapalan Surabaya (Persero) is one of the company’s shipyard in Indonesia. To improve the performance of the company, are needed anyway optimal performance of employees. The purpose of this study was to determine the effect of emotional intelligence on the performance of the supervisor and the mediating role of communication effectiveness on the influence of emotional intelligence on the performance of the supervisor. Samples from this study were all supervisors in the PT Dok dan Perkapalan Surabaya (Persero) amounting to 46 people. The data analysis technique used is the analysis method of Structural Equation Models with SmartPLS 2.0 M3.The results showed a positive and significant effect of the influence of emotional intelligence on the performance of the supervisor. However, the role of communication effectiveness is not significant in mediating the effects of emotional intelligence on the performance of the supervisor. Keywords: Emotional intelligence, supervisor performance, effectiveness of communication.